STRATEGI KOMUNIKASI PERSUASIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Nisfun Laily Zain (Jurnal Nomosleca, 2017)
Abstrack This research was conducted to find out what kind of personal communication strategy of teachers to improve student learning motivation in SMK JAWARA PGRI 1 Pasuruan. This research method using single case study with qualitative descriptive approach. This research is done by using object observation and interview to various informants that are directly related. From the research, it was found that personal communication done by the teacher to students and guardians, parents have a significant role in improving students' learning motivation. Personal communication approaches to students and parents need more seriousness and diligence than for teachers, because it takes up more energy, time, energy and also the cost necessary to communicate personally. Keywords: Personal communication, motivation, seriousness. DOI : https://doi.org/10.26905/nomosleca.v3i2.2034